Analisis Dampak Penggunaan Gadget Terhadap Prestasi Belajar Siswa - Wulandari, Fitri; Kamaruddin, Syamsu A. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The development of digital technology has brought about major changes in the world of education, including the increased use of gadgets by students as learning aids. This study aims to analyse the impact of gadget use on student learning achievement, both positive and negative. The study employed a qualitative descriptive method with data collection techniques through a literature review of the latest journals, books, and research reports, which were then analysed using content analysis techniques to identify patterns, findings, and conclusions related to the relationship between gadget use and learning achievement. The results of the study show that the targeted use of gadgets can increase motivation, expand access to information, and encourage student creativity. However, excessive and uncontrolled use has the potential to reduce concentration, trigger addiction, and have an impact on declining academic achievement. These findings emphasise the importance of parental and teacher guidance in regulating the duration, type of activity, and purpose of gadget use in order to provide optimal benefits for the student learning process.